Pre-aspiration outpatient ultrasound can accurately predict dry taps in prosthetic hips suspected of infection; a prospective study - Mirzaei, Alireza; Shafiei, Seyyed Hossein; Sadeghi-Naini, Mohsen; Rikhtehgar, Masih; Abolghasemian, Mansour (Frontiers in Surgery, 2024)
Aspiration represents the most potent method for exploring the potential occurrence of Periprosthetic Joint Infection (PJI). However, dry taps are common. While aspiration under ultrasound (US) guidance in the radiology department has become increasingly popular, hip aspiration is still routinely conducted in the operating room (OR) under X-ray guidance in numerous medical centers. When conducted within the confines of the OR, a dry tap aspiration not only subjects the patient to an unnecessary invasive procedure but also constitutes a substantial strain on OR time and resources. Our objective was to assess whether an outpatient US conducted before aspiration could reliably predict the likelihood of encountering a dry hip aspiration. In a prospective study, we enrolled 50 hips who were suspicious to PJI and slated for revision total hip arthroplasty and required hip aspiration. Before the aspiration procedure, we conducted an outpatient hip ultrasound (US) to assess the presence of fluid collection. Subsequently, all patients underwent aspiration under fluoroscopy in the OR, irrespective of the ultrasound findings. We then assessed the level of agreement between the ultrasound results and the outcomes of hip aspiration.The US exhibited a sensitivity of 95.7% (95% CI 69.8 to 91.8), a specificity of 74.1% (95% CI 52.8 to 91.8), a positive predictive value of 75.9% (95% CI 50.9 to 91.3), and a negative predictive value of 95.2% (95% CI 71.3 to 99.8) in predicting the success of aspiration. Therefore, preaspiration outpatient US demonstrates a high degree of accuracy in predicting dry taps in these patients. We recommend its incorporation into the hip aspiration procedure in medical centers where aspiration is performed in the operating room. In the broader context, these findings reinforce the preference for US-guided aspiration within the radiology department over X-rayguided aspiration in the operating room, since about ¼ of the positive USs for hip collection will lead to a dry tap if the aspiration is performed in the OR under fluoroscopy guidance.